The Levites and the boundaries of Israelite identity - Leuchter, Mark (Oxford University Press, 2017)
The biblical record attempts to present the Levites as a clerus minor under the Aaronides, a second class priestly order occupying a mediating role between them and the larger Israelite public. But scholars have long recognized that this literary presentation obscures a much more complicated reality pertaining to the origin of the Levites and their role in the development of Israelite religion. This study provides a renewed examination of the Levites as a social entity within ancient Israel, providing a detailed picture of their origins, their ideas, their response to adversity, and the deep impact of the traditions they forged and preserved in literary form.